Chemical sintering of TiO2 based photoanode for efficient dye sensitized solar cells using Zn nanoparticles. Issue 15 (15th October 2018) - Ahmad, Muhammad Shakeel; Pandey, A.K.; Rahim, Nasrudin Abd; Shahabuddin, Syed; Tyagi, S.K.
Abstract: Recombination reactions due to poor inter-particle contact at lower temperatures (< 450 °C) is a bottle neck for cost effective flexible dye sensitized solar cells (DSSCs). In this study, TiO2 sintering to Coble initial stage at low temperatures has been achieved with low melting point zinc (Zn) metal nanoparticles. Zn nanoparticles showed improved inter-particle contact by formation of necks due to high surface diffusion at relatively lower temperatures (200 °C). Addition of Zn nanoparticles showed comparable, rather improved efficiency at 200 °C compared to reference TiO2 photoanode fabricated at 450 °C due to neck formation and surface plasmonic resonance (SPR) effect. Morphological studies revealed high contact formation between TiO2 and Zn nanoparticles. Electrochemical impedance and Uv–vis spectroscopy showed improvements in charge transfer and light absorption activity respectively. Structural studies showed no any detectable change in phase due to high surface diffusion and capillary forces produced by Zn nanoparticles at the TiO2 /Zn interface. Graphical abstract: fx1